Anticancer efficacy of a nitric oxide‐modified derivative of bifendate against multidrug‐resistant cancer cells. Issue 6 (10th February 2016) - Ren, Zhiguang; Gu, Xiaoke; Lu, Bin; Chen, Yaqiong; Chen, Guojiang; Feng, Jiannan; Lin, Jizhen; Zhang, Yihua; Peng, Hui
Abstract: The development of multidrug resistance (MDR) not only actively transports a wide range of cytotoxic drugs across drug transporters but is also a complex interaction between a number of important cellular signalling pathways. Nitric oxide donors appear to be a new class of anticancer therapeutics for satisfying all the above conditions. Previously, we reported furoxan‐based nitric oxide‐releasing compounds that exhibited selective antitumour activity in vitro and in vivo . Herein, we demonstrate that bifendate (DDB)‐nitric oxide, a synthetic furoxan‐based nitric oxide‐releasing derivative of bifendate, effectively inhibits the both sensitive and MDR tumour cell viability at a comparatively low concentration. Interestingly, the potency of DDB‐nitric oxide is the independent of inhibition of the functions and expressions of three major ABC transporters. The mechanism of DDB‐nitric oxide appears to be in two modes of actions by inducing mitochondrial tyrosine nitration and apoptosis, as well as by down‐regulating HIF‐1α expression and protein kinase B (AKT), extracellular signal‐regulated kinases (ERK), nuclear factor κB (NF‐κB) activation in MDR cells. Moreover, the addition of a typical nitric oxide scavenger significantly attenuated all the effects of DDB‐nitric oxide, indicating that the cytotoxicity of DDB‐nitric oxide is as a result of higher levels of nitric oxide release in MDR cancer cells. Given that acquired MDR to nitric oxide donors is reportedly difficult to achieve and genetically unstable, compound like DDB‐nitric oxide may be a new type of therapeutic agent for the treatment of MDR tumours.